Experimental and computational analysis of failure mechanisms in unidirectional carbon fiber reinforced polymer laminates under longitudinal compression loading. (1st November 2018) - Sun, Qingping; Guo, Haiding; Zhou, Guowei; Meng, Zhaoxu; Chen, Zhangxing; Kang, Hongtae; Keten, Sinan; Su, Xuming
Abstract: This study investigates the failure mechanisms of notched unidirectional (UD) carbon fiber reinforced polymer (CFRP) laminates subjected to longitudinal compressive loading. A sequence of failure initiation and propagation is observed based on optical microscopy images of specimens during failure. The micrographs reveal that the main failure mechanism in UD laminates is fiber kinking failure. The influence of manufacturing defects and voids on fiber kinking mechanisms is also analyzed. The results show that the voids in the resin-rich area lead to kink-band splitting, while in some cases the voids cause the kink-band to deflect in a new direction depending on the location of the voids. The next focus of this study is to propose a computational micromechanics model considering local fiber waviness to study the fiber kinking failure mechanism. The computational results on kink-band formation and stress-strain response show good consistency with our experimental analysis. Finally, the failure envelopes of σ 11 -σ22 and σ 11 - τ 12 subjected to combined loading conditions are obtained from the computational model, which provide essential inputs for future theoretical failure criteria.